Flouting of Conversational Maxims Analysis of Characters and Social Contexts in “All The Bright Places” Movie - Aulia Zahra Tasyarasita; Agus Hari Wibowo (Surakarta English and Literature Journal, 2022)
This research is carried out to investigate the types of flouting of maxims and the strategies used by the characters that occur within the background of power and social distance contexts in "All The Bright Places" movie. Moreover, this research is also aimed to reveal the reasons behind the execution of the flouting of maxims. This research is employed qualitative research. The data source of this research is presented in the form of words, phrases, and sentences containing flouting of the maxims obtained from the characters' utterances in the movie. The data were analyzed using Grice's cooperative principle theory, Cutting's theory of strategies to flout the maxims, Leech's theory of illocutionary functions of politeness, and Brown and Levinson's theory of social context. The research findings concluded that four types of flouting maxims are found in the characters' utterances: flouting the maxim of quantity, flouting the maxim of quality, flouting the maxim of manner, and flouting the maxim of relevance. Only three reasons for flouting the maxims were found of four types: competitive, collaborative, and conflictive. The most frequently used flouting maxim is flouting the maxim of quality which is aligned with the competitive reason as the most commonly used reason to flout the maxim.